ANALYSIS OF STUDENT SATISFACTION LEVEL IN THE QUALITY OF BIMA LIBRARY SERVICES - Nurul Iman; Intisari Haryanti (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2020)
Good or bad service, of course, affects the satisfaction of library visitors. The level of visits increases when visitors feel their expectations are met and satisfied with the services provided. On the other hand, various complaints were expressed in relation to services provided by the regional library of the city of Bima, this was an important and interesting reason. So the researchers aimed to choose this study was to find out and explain how the level of visitor satisfaction with service quality in the area of ​​the city of Bima. The population in this study were visitors visiting the library in the city of Bima, with a sample of 96 people. To process the data from the questionnaire results is by descriptive analysis. The findings show that visitors have high satisfaction with the quality of services available in the Bima city library. Keywords: satisfaction, service quality.